Microclimate of Developed Peatland of the Mega Rice Project in Central Kalimantan - Jaya, Adi; Inoue, Takashi; Limin, Suwido Hester; Darung, Untung; Banuwa, Irwan Sukri (JOURNAL OF TROPICAL SOILS, 2010)
Microclimate of Developed Peatland of The Mega Rice Project in Central Kalimantan (A Jaya,T Inoue, SH Limin, U Darung and IS Banuwa): In Indonesia peatland covers an area of 16 to 27 Mha and this ecosystem is vitally linked to environmental and conservation issues, as well as its economic value for human survival. These peatlands are, however, the subject of various land use pressures, including forestry, agriculture, energy and horticulture. A field study was carried out 6 years after the end of failed peatland development project shows that inappropriate and unsustainable forms of peatland management have resulted in degradation of the natural forest vegetation, draw-down of the peat water table, increase of peat surface and air temperatures and recurrent surface and ground fires. Implications of microclimate for possible restoration options.